Considerations for development of therapies for cutaneous neurofibroma. (10th July 2018) - Verma, Sharad K.; Riccardi, Vincent M.; Plotkin, Scott R.; Weinberg, Hubert; Anderson, R. Rox; Blakeley, Jaishri O.; Jarnagin, Kurt; Lee, James
Abstract : Objective: The only therapies currently available for cutaneous neurofibromas (cNF) are procedural. The goals of the Therapies Development Working Group were to (1) summarize currently available treatment options for cNF, (2) define key considerations for drug discovery and development generally, and specifically for cNF, and (3) outline recommendations for the successful development of medical therapies for cNF. Methods: The subgroup reviewed published and unpublished data on procedural, drug/device, and medical treatment approaches utilized for cNFs via literature search. The team defined disease- and patient-specific factors to consider for therapies development in a series of consensus meetings. Results: The team identified 5 approaches entailing procedural and drug/device methods currently under study. There have been 4 clinical studies exploring various interventional therapies, from which outcomes were highly variable. The team identified 4 key factors to prioritize during the development of products for the treatment for cNF: safety, anatomic distribution of cNF, numbers of tumors to be treated, and route of administration. Conclusions: The number, size, and distribution of cNF is highly variable among patients with NF1 and it is possible that different phenotypes will require different drug development paths. The nonfatal nature of the disease and relatively limited patient numbers suggest that for any product to have a higher likelihood of acceptance, it will have to (1) demonstrate an effect that is clinically meaningful, (2) have a safety profile conducive to long-term dosing, and (3) have a low manufacturing cost.